Dynamic response of large-section inclined shallow-buried pipe tunnel under train loads - Cui, Guo-Jing; Xie, Jiang-Sheng; Sun, Yin-hao; Tian, Xiao-xu; Meng, Chen (Frontiers in Earth Science, 2023)
To ensure the normal passage of an ascending road during the construction of a pipe-jacking tunnel, trains generally run at low speeds during the construction phase and adopt normal speeds later. Using Jingjiu Road, Xi 'an, China, as an engineering case, this study evaluated and predicted the dynamic response of a tunnel structure and soil mass when trains run at low to normal speeds. When the train speed was controlled in the range of 30–60 km/h, the soil deformation change rate around the shallow-buried pipe-jacking tunnel was 0.41%. The maximum tensile stress growth rate of the pipe-jacking tunnel structure was 0.037%, the maximum compressive stress growth rate was 0.128%, and the maximum increase in the stress of the pipe-jacking structure was 1.82%. Thus, the soil and structure of the pipe-jacking tunnel were in a safe-stress state. The results show that the influence of train speed on soil and structural stress is small and can be ignored.